Location and pre-excavation information (Scottish Historical and Archaeological Internet Reports, 2004)
Details of site location and information available prior to the commencement of work. A total of 2908 pieces of flaked stone had been recovered and some of the material indicated a potentially early Mesolithic date. For this reason a decision was made to excavate.